Innovations in Enterprise Information Systems Management and Engineering 4th International Conference, ERP Future 2015 - Research, Munich, Germany, November 16-17, 2015, Revised Papers - Felderer, Michael; Piazolo, Felix; Ortner, Wolfgang; Brehm, Lars; Hof, Hans-Joachim (Lecture Notes in Business Information Processing,, 2016)
This volume presents the revised and peer reviewed contributions of the 'ERP Future 2015' conference held in Munich, Germany on November 16-17, 2015. The ERP Future 2015 Research conference is a scientific platform for research on enterprise information systems in general and specifically on core topics like business process management (BPM), business intelligence (BI) and enterprise resource planning (ERP) systems. Besides the scientific community the event also addresses businesses developing, implementing and using enterprise information systems. The 7 full papers and 5 short papers accepted for ERP were selected from 23 submissions. The papers consider topics in education in enterprise systems; business process management; enterprise systems and solution providers; and IT-trends.